COMPARISON OF THE EFFECTIVENESS OF DIFFERENT ASSESSMENT METHODS IN TEACHING PHARMACEUTICAL CHEMISTRY AT A MEDICAL HEI - Velyka, Alla; Kropelnytska, Yulia; Garvasiuk, Oleksandra (SWorldJournal, 2025)
An effective assessment system in pharmaceutical chemistry should aim at developing critical thinking, problem-solving skills, analytical abilities, and professional personal qualities necessary for successful work in the pharmaceutical market. The applic